MANAJEMEN REKRUTMEN DAN PENEMPATAN KERJA TERHADAP KINERJA KARYAWAN PT. SULOTCO JAYA ABADI TANA TORAJA - Buratasik, Siska; Roswiyanti (Jurnal Pendidikan Sang Surya, 2025)
Improving employee performance is essential for promoting companyprogress in facing an unstable business environment. This study aims to determine theeffect of recruitment and job placement on employee performance at PT. Sulotco JayaAbadi. The research employs a quantitative approach with a saturated samplingmethod, involving 50 employee respondents. Data collection techniques includeobservation, documentation, questionnaires, and interviews, while data analysis isconducted using validity and reliability tests, multiple linear regression, t-test, and Ftest,with the assistance of SPSS version 25. The results show that recruitment has asignificant effect on employee performance, as indicated by a t-value of 2.613 > ttable2.011 and a significance level of 0.012 < 0.05 (H1 accepted). Job placement alsosignificantly affects employee performance, with a t-value of 3.942 > t-table 2.011 anda significance level of 0.000 < 0.05 (H2 accepted). The F-test results indicate thatrecruitment and placement simultaneously have a significant effect on performance(F-value 23.161 > F-table 3.20; sig. 0.000 < 0.05), thus the hypothesis is accepted.